Impelementasi dan Penerapan Hukum Waris Islam di Indonesia - Ester Simanjuntak, Octa Vioni,Sri Hadiningrum, Filzah Irshadi, (Mediation : Journal of Law, 2023)
The law that discusses property matters in legal science is called inheritance law. Provisions regarding Inheritance Law in Indonesia are regulated in Islamic Inheritance Law, Customary Inheritance Law, and Dutch Inheritance Law (Inheritance Law of the Civil Code). In terms of regions in Indonesia and the diversity of culture, religion and customs in the kinship system in each region, it influences the application of Inheritance Law in Indonesia. However, problems often arise between the laws that apply in religion and the implementation of local regional customs. The author discusses the application of Islamic Inheritance law in Indonesia. Settlement of inheritance through peace is a good instrument for maintaining the integrity of family relationships, in addition to avoiding or resolving disputes, feuds, even enmity. So that harmony and kinship or kinship community will be maintained in society. In this research, the author used a qualitative descriptive approach. Qualitative descriptive research. The research method is also combined with literature research methods. In this research the method is access to standard law or related books, and apart from human rights books which are important for the discussion of this article, information from research journals. on this topic and research from websites associated with this title. The nature of the study is still temporary, it is possible that there are still studies that will continue to be updated to make them even better.